Multiparametric MRI Findings association with Pathological Features and hormonal secretion in Patients with Pituitary Macroadenoma: A Comprehensive Study - Haghighi-Morad, Maryam; Bidari Zerehpoosh, Farahnaz; Jahangiriyan, Mohammad Amin (Novelty in Biomedicine, 2025)
Background: Pituitary macroadenoma is a global health concern. Advanced imaging techniques, such as multiparametric magnetic resonance imaging (MRI), have emerged as valuable tools for comprehensively evaluating macroadenomas. This study aimed to evaluate the association between multiparametric MRI findings, pathological features, and type of secretion in patients with pituitary macroadenoma. Materials and Methods: This cross-sectional study evaluated the association between multiparametric MRI findings and pathological features in patients with pituitary macroadenoma. Patients with pituitary macroadenoma referred to Loghman Hakim Hospital (Tehran-Iran) in 2023 were assessed. Preoperative MRI, including T1W, T2W, DWI, ADC, and CE-MRI, were evaluated for signal intensity, maximum diameter, and tumoral extension. The association between the results of MR imaging and the pathologic findings of the resected macroadenoma was assessed. Results: Forty-five patients were assessed. The mean age was 48.22 ± 14.58 years, and 55.6% of the patients were male. Most patients (48.9%) had isointense lesion in T1W, and most lesions (57.8%) had heterogeneous signals in T2W. Apparent diffusion coefficient levels (ADC) had no diagnostic value for predicting pathologic subtypes. The most invasion was to the infrasellar among macro adenomas (P-value: 0.037). Among patients with gonadotroph pathology results, invasion to the third ventricle with heterogeneous signal on T2 was more common (P-values<0.05). The mean tumor volume is higher in the Prolactin (PRL) secreting type compared to other categories (P-value: 0.002). Conclusion: Multiparametric MRI helps predict the pathological diagnosis of pituitary macroadenoma.